Model of Community Capacity In Facing Disaster Using Ordinal Logistic Regression Analysis - Jaka Nugraha; Fitri Nugraheni; Irwan Nuryana Kurniawan (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2016)
Indonesia is geographically a country with potential natural disasters which is high for various types of disasters such as floods, earthquakes, landslides, drought and volcanoes. A regional disaster risk reduction can be done with increase the capacity of government and communities in disaster mitigation. On this paper discusses the formulation of community capacity models in the face of disaster using ordinal logistic regression analysis. The regression model was prepared using three dependent variables are (i) general knowledge of risk reduction natural disaster symbolized by Y1 (ii) general knowledge possessed about how to save the family when a natural disaster is symbolized by Y2 (iii) efforts to increase citizens' awareness of natural disasters by related parties symbolized by Y3. The dependent variables Y1 and Y2 are influenced by the Knowledge Factor and Factor Plan of Action. While the dependent variable Y3 is influenced by Factor leadership and programs, and Facility Factors.